The Influence of Entrepreneurial Leadership, Human Capital, and Organizational Commitment on Business Performance - the Mediating Role of Entrepreneurial Orientation: A Study At Pt Panca Putra Gilang Mandiri - Andrian Louise Tandra; Eddy (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the influence of Entrepreneurial Leadership, Human Capital, and Organizational Commitment on Business Performance, with Entrepreneurial Orientation as a mediator at PT Panca Putra Gilang Mandiri (PT PPGM), where the observed phenomenon is performance inconsistencies, supposedly caused by unclear leadership vision and slow innovation. The research's theoretical framework was developed to define all five variables. Literature reviews offer some explanations on the associations among variables. Based on empirical explanations, ten research hypotheses were formulated to test direct and mediating relationships. This study used a quantitative method with a causal approach. A census sample of all 43 employees at PT PPGM was used. Primary data was collected via questionnaires and analyzed using PLS-SEM with SmartPLS 4 software. The measurement model has proved valid and reliable. Hypothesis testing (p<0.05) supported H1 (EL?BP), H2 (EL?EO), and H4 (HC?EO). However, H7 (EO?BP) and all mediation hypotheses (H8-H10) were rejected. The model explained 60.2% of the variance in Business Performance. Based on the IPMA analysis, the most critical yet underperforming areas include innovativeness and proactiveness items, which aligns with the lowest mean scores found in vision communication and innovation. Therefore, it is strongly recommended that PT PPGM prioritize fixing its innovation barriers to create a formal, fast-track system for new ideas. Moreover, future researchers are recommended to integrate another mediator on EO-BP associations.